Evaluation of Different Range-Doppler Processing Techniques for OFDM-Based DVB-T2 Passive Radar - Stephen Paine; W. P. Francois Schonken; Daniel W. O'Hagan; Christof Schupbach; Jan Pidanic; Josef Jordan (IEEE Access, 2025)
There are many papers investigating the processing stages required for the first-generation terrestrial Digital Video Broadcast, DVB-T, and the advantages and disadvantages of each technique. As the world moves towards the deployment of the second generation (DVB-T2) standard, there is a gap in the literature focusing on applying these processing steps in the DVB-T2 context. One of the advantages of the DVB-T2 standard is the higher level of flexibility in transmission. This flexibility poses challenges to passive radar (PR) designers that needs to be addressed. One of the major differences between DVB-T and DVB-T2 is the increased number of pilot configurations and higher data rates (effectively larger FFT sizes). This paper compares the two main processing techniques, mismatched filtering and inverse filtering in the DVB-T2 context. Using real world signal parameters, extracted from recorded data, the application of each processing technique is clearly demonstrated, illustrating the advantages and disadvantages for each. A novel approach to resolving Doppler ambiguities that appear when using inverse filtering for DVB-T2 based passive radar, is then presented and its application demonstrated.